KAJIAN TENTANG KUALITAS PELAYANAN, KEPUASAN DAN CITRA PERGURUAN TINGGI - Fanggidae, Paulus Yulius; Juniarto, Antonius (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The client is the "king" this expression emphasizes that the client must be accepted or served as a "king" and of course implies a willingness to present the king (in this case the client) with his best aspects. The service world dimension is a variable that needs to be considered, as well as understanding the consumption behavior of target consumers in order to provide and deliver what consumers need. Higher education service providers need to improve service quality with various supporting functions to create an attractive atmosphere (mood) when delivering service at a service summit. Current operational activities of educational institutions must be able to satisfy the needs and desires of customers (students), provide the best possible service amidst increasingly fierce competition and increasingly intelligent consumers who tend to be less "loyal" and enthusiastic. transfer your activity. loyalty to service providers that align with their vision. Increasingly fierce competition has forced many educational service providers to invest and develop in providing and providing quality services by combining various aspects such as people, equipment, use of technology and other programs that facilitate the "delivery process" of educational services as an inseparable part. part of the organization's efforts to implement a commitment to continuous quality improvement. This requires systematic support to conduct surveys on service quality, satisfaction and institutional reputation to obtain a true and accurate picture, which is then followed up to create a competitive advantage that becomes a strength for continued growth and sustainability